Homeland security : assessing the first five years - Chertoff, Michael, 1953- (University of Pennsylvania Press, 2009)
Michael Chertoff outlines a long-term strategy for protecting America from terrorist attacks and preparing for effective responses to man-made and natural disasters. The former homeland security secretary also urges the nation to resist complacency, maintain its resolve, and build on past successes.